2000
DOI: 10.1099/00221287-146-11-2909
|View full text |Cite
|
Sign up to set email alerts
|

GcvA binding site 1 in the gcvTHP promoter of Escherichia coli is required for GcvA-mediated repression but not for GcvA-mediated activation

Abstract: GcvA binds to three sites in the gcvTHP control region, from base N34 to N69 (site 1), from base N214 to N241 (site 2) and from base N242 to N271 (site 3).Previous results suggested that sites 3 and 2 are required for both GcvAdependent activation and repression of a gcvT ::lacZ fusion. However, the results were less clear as to the role of site 1. To determine the role of site 1 in regulation, single and multiple base changes were made in site 1 and tested for their ability to alter GcvA-mediated activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Plasmids pGS420 and pGS428 were derived from pGS318 and carry a 15 bp and a 25 bp insert between GcvA binding site 3j2 and site 1, respectively (Stauffer & Stauffer, 1998b). Plasmid pGS357 has a 4 bp change in site 1 that reduces GcvA binding to site 1 about twofold (Wilson et al, 1995 ;Wonderling et al, 2000). These plasmids were used as the starting templates in PCR reactions with primers containing XbaI sites and sequences complementary to gcv upstream and downstream the GcvA binding sites.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plasmids pGS420 and pGS428 were derived from pGS318 and carry a 15 bp and a 25 bp insert between GcvA binding site 3j2 and site 1, respectively (Stauffer & Stauffer, 1998b). Plasmid pGS357 has a 4 bp change in site 1 that reduces GcvA binding to site 1 about twofold (Wilson et al, 1995 ;Wonderling et al, 2000). These plasmids were used as the starting templates in PCR reactions with primers containing XbaI sites and sequences complementary to gcv upstream and downstream the GcvA binding sites.…”
Section: Methodsmentioning
confidence: 99%
“…1). All three of these sites are required for repression of the operon, while only sites 2 and 3 appear to be necessary for activation (Wilson et al, 1995 ;Wonderling et al, 2000). In addition, DNase I footprint studies with GcvA showed hypersensitive cleavage sites in the region between the upstream sites 3j2 and the downstream site 1 when GcvA was bound to these sites.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations